Environmental Sustainability and its Growth in Malaysia by Elaborating the Green Economy and Environmental Efficiency - Kasayanond, Arunee; Umam, Rofiqul; Jermsittiparsert, Kittisak (International Journal of Energy Economics and Policy, 2019)
Numerous countries have sorted out energy awards as an instrument to promote energy efficiency (EE), to contribute towards energy sustainability and to give a component to associations to constantly hunt benchmark and recognize activities and best practices in EE. Most of companies to invest in the reusing and reuse of materials, the environmentally inviting technology, inward training on green economy, the remainder of the electorate and the buy and utilization of materials with less impact essentially in light of the fact that they trust that investment to guarantee the safeguarding of nature around. It is additionally a marker of an effective environmental sustainability in Malaysia dependent on the reactions are broke down from an assortment of high technology-based companies working in Kedah, Malaysia. Malaysia is focused on cultivating the development of a clean and efficient economy; that is, a "green" economy. This implies encouraging the development of green businesses and green items, which thus will make "green jobs." At the fundamental level, there exists a misallocation of resources. As Malaysia advances greater environmental awareness, it is imperative to establish national benchmarks by which to measure progress toward a greener economy. This investigation tries to find the condition of knowledge in Malaysia on the green economy. The result additionally shows that an expansion in the prioritizing green economy anticipated by the companies working in Malaysia will prompt increment in green monetary sustainability. This suggests the progress towards the green economy in Malaysia is likewise impacted by the view of its significance later on. The investigation uncovers that expansion in green economy awareness among the firms will prompt increment in the level of environmental sustainability, in this way improving the present condition of green economy in Malaysia. Keywords: Green Economy, Environmental Efficiency, Sustainability, Energy Efficiency, Malaysia, companies, growth JEL Classifications: Q55, Q50 DOI: https://doi.org/10.32479/ijeep.8310